How Victims of Strangulation Survived: Enhancing the Admissibility of Victim Statements to the Police When Survivors are Reluctant to Cooperate - Brady, Patrick Q. (Violence against women, 2022)
Holding perpetrators accountable for family violence is challenged when survivors are reluctant to testify. In light of recent Supreme Court precedents limiting the admissibility of statements to law enforcement in victimless prosecutions, the current study examined 130 cases of nonfatal strangulation (NFS) to determine whether case characteristics and themes across survivors’ on-scene statements can help prosecutors combat common legal defenses raised when victims are unavailable for trial. The history of prior violence and how only 6% of perpetrators stopped strangling victims on their own suggests that NFS complaints should be investigated as an attempted homicide until evidence suggests otherwise.